Natalizumab versus fingolimod and dimethyl fumarate in multiple sclerosis treatment. Issue 2 (9th December 2018) - Vollmer, Brandi L.; Nair, Kavita V.; Sillau, Stefan; Corboy, John R.; Vollmer, Timothy; Alvarez, Enrique
Abstract: Objective: To compare 2‐year effectiveness and discontinuation of natalizumab (NTZ) versus fingolimod (FTY) and dimethyl fumarate (DMF) in the treatment of multiple sclerosis (MS). Methods: Patients prescribed NTZ, FTY, or DMF at the Rocky Mountain MS Center at University of Colorado were identified. Clinician‐reported data were retrospectively collected. Outcomes include a composite effectiveness measure consisting of new T2 lesion, gadolinium‐enhancing lesion, and/or clinical relapse, individual effectiveness outcomes and discontinuation over 2 years. Logistic regression was used for data analysis on patients matched by propensity scores and using ATT doubly robust weighting estimator. Results: A total of 451, 271, and 342 patients were evaluated on NTZ, FTY, and DMF over 2 years, respectively. Patients had a mean age of 39.8 (NTZ), 42.5(FTY), and 45.8 (DMF) years; were predominantly female (76.7% NTZ; 72.0% FTY; 69.6% DMF); and had a mean MS disease duration of 11–12 years for all groups. At ≤24 months, 22.2%, 34.7%, and 33.6% experienced a new T2 lesion, gadolinium‐enhancing lesion, and/or clinical relapse on NTZ, FTY, and DMF, respectively. Using ATT doubly robust weighting estimator, FTY versus NTZ and DMF versus NTZ had an odds ratio of 2.00 (95%CI:[1.41–2.85], P < 0.001) and 2.38 [95% CI: 1.68–3.37], P < 0.001) respectively, for experiencing a new T2 lesion, gadolinium enhancing lesion, and/or clinical relapse. At ≤24 months, 32.6%, 34.3%, and 47.1% discontinued NTZ, FTY, and DMF, respectively. The majority of discontinuations were due to becoming JCV positive(12.6%) for NTZ and due to adverse events for both FTY(17%) and DMF(24.0%). Interpretation: NTZ appears to be more effective and tolerable than FTY and DMF.